2017
DOI: 10.1177/1010428317694565
|View full text |Cite
|
Sign up to set email alerts
|

Coptisine-induced cell cycle arrest at G2/M phase and reactive oxygen species–dependent mitochondria-mediated apoptosis in non-small-cell lung cancer A549 cells

Abstract: This study aimed to explore the effect of coptisine on non-small-cell lung cancer and its mechanism through various in vitro cellular models (A549). Results claimed significant inhibition of proliferation by coptisine against A549, H460, and H2170 cells with IC 50 values of 18.09, 29.50, and 21.60 µM, respectively. Also, coptisine exhibited upregulation of pH2AX, cell cycle arrest at G2/M phase, and downregulation of the expression of cyclin B1, cdc2, and cdc25C and upregulation of p21 dose dependently. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
1
27
2
Order By: Relevance
“…Besides, coptisine (12.5‐50 μmol/L, 48 hours) not only promoted DNA damage of A594 cell through increase pH2AX protein (DNA damage marker) level but also triggered the occurrence of apoptosis by up‐regulating ROS, caspase‐3/‐9, Bax/Bcl‐2 and PARP cleavage . Consistent with that in A549 cell, coptisine (2.5‐40 μmol/L, 4 hours; 25‐50 μmol/L, 24 hours) as well modulate ROS caspase‐3/‐9 and Bax/Bcl‐2 in H2O2‐stimulated EA.hy926 and NCI⁃H1650 cells …”
Section: Anti‐cancer Propertysupporting
confidence: 57%
See 1 more Smart Citation
“…Besides, coptisine (12.5‐50 μmol/L, 48 hours) not only promoted DNA damage of A594 cell through increase pH2AX protein (DNA damage marker) level but also triggered the occurrence of apoptosis by up‐regulating ROS, caspase‐3/‐9, Bax/Bcl‐2 and PARP cleavage . Consistent with that in A549 cell, coptisine (2.5‐40 μmol/L, 4 hours; 25‐50 μmol/L, 24 hours) as well modulate ROS caspase‐3/‐9 and Bax/Bcl‐2 in H2O2‐stimulated EA.hy926 and NCI⁃H1650 cells …”
Section: Anti‐cancer Propertysupporting
confidence: 57%
“…31,32 Similar anti-cancer property of coptisine was observed in liver 33,34 In the next study, authors revealed that coptisine and NCI•H1650 cells. [38][39][40] Several studies have established that coptisine exerts ameliorative effect on cancer in in vivo model. Cao Another study, which was aimed to investigate the effect of coptisine on liver cancer-associated acute liver failure, verified that coptisine (37.5-150 mg/kg, oral, once daily for 7 days) down-regulated TLR-4 expressions and apoptotic protein level.…”
Section: Anti -C An Cer Propert Ymentioning
confidence: 99%
“…Many anti-cancer agents reduce malignant growth by arresting the cell cycle at the G1/S or G2/M phases [ 53 ]. According to previous studies, cell cycle arrest, particularly G2/M phase, might be a useful therapy to prevent the proliferation of cancer cells [ 54 ]. The CDK1, Cyclin B and Cdc25C are essential for inducing G2/M cycle phase, which could enhance the dividing of a cell into two [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As analyzed by flow cytometry (Figures 9A and S8), radiation (6 Gy) alone slightly caused 19.87% of G2/M phase arrest, which might induce apoptosis of cells. 49,50 In addition, HABi 2 O 3 NPs (from 0 to 200 μg/mL) activated apoptotic cell death from 0.446% to 2.34%, as reflected by the sub-G1 proportions. 51 However, the combination of HA-Bi 2 O 3 NPs and radiation dose-dependently increased the extent of G2/M phase arrest and cell apoptosis.…”
mentioning
confidence: 99%